Newspapers in transition American dailies confront the digital age - Cox, Jim 1939- (McFarland, 2014)
"The impact of cyberspace on newsprint journalism is at the core of this text"..
Includes bibliographical references (pages 209-214) and index
Keywords: Geschichte; Newspaper publishing -- United States -- History -- 21st century; Newspaper publishing -- Technological innovations -- United States; Journalism -- Technological innovations -- United States; Electronic newspapers -- United States -- History -- 21st century; Digitalisierung; Neue Medien; Zeitung; Technischer Fortschritt; USA